2016
DOI: 10.1038/srep27532
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine administration prevents retinal neuroinflammation and loss of retinal ganglion cells in an animal model of glaucoma

Abstract: Glaucoma is the second leading cause of blindness worldwide, being characterized by progressive optic nerve damage and loss of retinal ganglion cells (RGCs), accompanied by increased inflammatory response involving retinal microglial cells. The etiology of glaucoma is still unknown, and despite elevated intraocular pressure (IOP) being a major risk factor, the exact mechanisms responsible for RGC degeneration remain unknown. Caffeine, which is an antagonist of adenosine receptors, is the most widely consumed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 63 publications
3
45
0
Order By: Relevance
“…Modeling ocular hypertension in vitro increased the expression of TSPO and MHC‐II in retinal neural cells, consistent with a response of microglia to elevated pressure. Also, A 2A R antagonist prevented this increase, suggesting that microglial A 2A R controls neuroinflammation, as has been suggested previously (Boia et al, ; Madeira et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Modeling ocular hypertension in vitro increased the expression of TSPO and MHC‐II in retinal neural cells, consistent with a response of microglia to elevated pressure. Also, A 2A R antagonist prevented this increase, suggesting that microglial A 2A R controls neuroinflammation, as has been suggested previously (Boia et al, ; Madeira et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…Coffee pulp contains caffeine (Salinas et al 2014), which is widely used for its different physiological effects. For example, caffeine is used in children with apnea as an inhibitor of adenosine receptors and as a modulator of inflammatory processes to decrease the quantity of neutrophils by inhibiting IL-10 (Chavez et al 2011) and TNF-α expression (Horrigan et al 2004), and in laboratory animals as an anti-inflammatory factor for the prevention of glaucoma (Madeira et al 2016). Li et al (2011) observed that caffeine decreased the chemotaxis and phagocytic activity of neutrophils in pig spermatozoa.…”
Section: Resultsmentioning
confidence: 99%
“…2H). Finally, stimulating microglial activation and inflammation in the rat retina in vivo by intravitreous injection of LPS or performing retinal ischemia-reperfusion injury (36)(37)(38)(39)(40) reduced SVCT2 abundance in the retina (Fig. 2, I and J).…”
Section: A01/00mentioning
confidence: 97%